Postmortem evaluation of the use of diaphragmatic excursus in assessment of pulmonary emphysema in coal miners. Issue 3 (May 1972) - McKenzie, H. I.; Outhred, K. G.; Glick, M.
Abstract : In a series of 89 subjects (all coal miners or ex-coal miners) a high order of correlation has been found between diaphragmatic excursus measured within five years of death and the necropsy assessment of emphysema in the lungs. In the absence of other common factors that reduce the range of movement of the diaphragm, measurements of diaphragmatic excursus provide a statistical prediction of the severity of emphysema. The individual variance, however, is such that this assessment should be used only as part of a range of clinicoradiological, physiological, and electrocardiographic indicators of emphysema severity. Evidence is presented to show that the movement of the diaphragm is restricted in the predominantly emphysematous members of the series but approaches full normal range in the group with predominant chronic obstructive bronchitis.